Surgical management of bronchiectasis - Bhandari, Shanker; Gurung, Dinesh; lslam, Kazi Saiful; Razzaque, -; Aftabuddin, Md.; Adhikary, Asit Baran (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Bronchiectasis is the permanent dilatation of the bronchi due to destruction of bronchial wall. Bronchiectasis still remains a serious problem in developing countries despite of modern medical facilities. Objectives: This study aims to demonstrate our surgical experience for bronchiectasis and analyze the risk factors related with the surgery outcome. Methods: Hospital based analyses of 39 patients were done who were underwent surgery for bronchiectasis and were on follow up in National Institute of Diseases of Chest hospital (NIDCH) in September 2014 to February 2015 were included in this study. All 39 patients had surgery for the bronchiectasis in the period of January 2014 to December 2014. Results: The mean age of the patients were 22.2 years. Twenty four patients were females and 15 were male. Symptoms were recurrent infection with cough, copious sputum in all patients and hemoptysis in 31 patients. The etiology was recurrent childhood infection in 17 patients, pneumonia in 11 patients, PTB in 6 patients, Aspiration in 2 patients, foreign body obstruction in 1 patient, and unknown etiology in 2 patients. Chest x-ray, CT scan and rigid bronchoscope were done for all patients. Bronchiectasis was left-sided in 17 patients. It was mainly confined to the lower lobes either alone in 9 patients and in conjunction with middle lobe or lingual in 8 patients. Indications for resection were failure of conservative therapy in 22 patients, hemoptysis in 8 patients, destroyed lung in 9 patients. Surgery was lobectomy in 24 patients, Bilobectomy in 5 patients, and pneumonectomy in 10 patients. Complications occurred in 10 patients with no operative mortality. Thirty four patients had relief of their preoperative symptoms after surgery in follow up periods. Conclusions: Surgical resection for bronchiectasis should be reserved for patients with localised disease who have failed medical management and have persistent symptoms that negatively affect their quality of life.